2018
DOI: 10.1016/j.orggeochem.2017.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxygenase-induced autoxidative degradation of terrestrial particulate organic matter in estuaries: A widespread process enhanced at high and low latitude

Abstract: There exists a substantial amount of research on abiotic (e.g. photochemical) degradation pertaining to organic matter (OM) in the marine realm. While recent research has shown its importance in the degradation of terrestrial particulate OM (TPOM), the mechanisms involved in the induction of autoxidation in estuaries remain unclear. In this study, we propose for the first time the involvement of lipoxygenase (LOX) activity in the induction of autoxidation in mixed waters. The observation of unusual profiles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 91 publications
(124 reference statements)
1
17
0
Order By: Relevance
“…It was previously observed that autoxidation of terrestrial higher plants was less efficient in temperate zones than at low or high latitudes . The low autoxidation percentages of amyrins measured in the samples investigated (Table ) give good support to these previous observations.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…It was previously observed that autoxidation of terrestrial higher plants was less efficient in temperate zones than at low or high latitudes . The low autoxidation percentages of amyrins measured in the samples investigated (Table ) give good support to these previous observations.…”
Section: Resultssupporting
confidence: 85%
“…The ketones 7 and 8 were thus proposed as tracers of abiotic degradation (autoxidation) of terrestrial higher plants in the marine realm . Although very high proportions of these tracers could be easily detected by GC/MS operating in selected ion monitoring (SIM) mode in particulate matter and sediment samples collected in the Arctic and tropical zones, their quantification in samples where terrestrial organic matter is present in lesser proportions remains more problematic.…”
Section: Introductionmentioning
confidence: 99%
“…However, here we show that autoxidative degradation of IP 25 may occur under more 'forced' conditions and such processes may also take place in Arctic surface sediments. Indeed, due to recent evidence of strong lipoxygenase activity (a well-known source of radicals; Fuchs and Spiteller, 2014) in bacteria associated with ice algae (Amiraux et al, 2017) and in terrestrial particulate organic matter discharged from Arctic rivers (Galeron et al, 2018), autoxidative degradation reactions can even be dominant in Arctic sediments (Rontani et al, 2012(Rontani et al, , 2017, despite the low temperatures. The autoxidation of IP 25 in sediments possessing a thick oxic layer, where the contact of ice algal detritus with oxygen may be relatively long, therefore represents a viable degradation pathway of this biomarker in near-surface sediments.…”
Section: Degradation Of Ip 25 Epi-brassicasterol and 24methylenechomentioning
confidence: 99%
“…This high autoxidation efficiency likely reflects the enhanced photooxidation of senescent vascular plants in the region (thus yielding high amounts of hydroperoxides), together with high lipoxygenase activity (a potential source of radicals; Fuchs and Spiteller, 2014). Indeed, the latter mechanism has recently been observed in sinking particles dominated by ice algae (Amiraux et al, 2017) and in particles discharged from the Mackenzie River (Galeron et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the oxidation products of monounsaturated fatty acids appear to be especially useful for differentiating the involvement of photo-and autoxidative degradation processes in suspended and sinking particulate matter and bottom sediment samples (for a review see Rontani, 2012). More recently, analysis of these compounds provided evidence of lipoxygenase-induced degradation in suspended (Galeron et al, 2018) and sinking (Amiraux et al, 2017) particles.…”
Section: Introductionmentioning
confidence: 99%